A Comprehensive Study of Mobile Computing in Telemedicine - Atta-ur-Rahman; Dash, Sujata; Kamaleldin, Mahi; Abed, Areej; Alshaikhhussain, Atheer; Motawei, Heba; Amoudi, Nadeen Al; Abahussain, Wejdan; Sultan, Kiran (Advanced Informatics for Computing Research, 2018)
Telemedicine is the concept coined by the use of telecommunication and information technology to cater healthcare facilities to patients from a far-off place. Telemedicine has exhibited an efficient mechanism to face the hurdles of helthcare to provide superior quality medical services from specialized doctors situated in urban areas to communities particularly located in rural or remote areas. This research paper will introduce several telemedicine applications that helped easier access to specialist doctors, improved satisfaction level of patients, and better clinical outcomes. The first section will define the architecture of telemedicine. Secondly, the second section will represent different telemedicine applications. Lastly, the study will also depict opposing views on the technology of telemedicine and possible solutions.